Species of Proteocephalus Weinland, 1858 (Cestoda: Proteocephalidae) from cyprinid fishes in North America - Scholz, T; Hanzelová, V (The Journal of parasitology, 1999)
A taxonomic study of Proteocephalus species parasitizing cyprinid fishes in North America, namely Proteocephalus ptychocheilus Faust, 1920 and Proteocephalus cobraeformis Haderlie, 1953, has demonstrated their conspecificity with Proteocephalus torulosus (Batsch, 1786), a common parasite of cypriniform fishes (Cyprinidae and Cobitidae) in the Palaearctic Region. Proteocephalus ptychocheilus and P. cobraeformis are considered junior synonyms of P. torulosus.
Keywords: Cestoda; Cyprinidae; North America; Fish Diseases; Animals; cestodózy; Cestode Infections; zvířata; nemoci ryb; Severní Amerika